The Failure of Competition in the Credit Card Market in Turkey: The New Empirical Evidence - Ahmet Faruk Aysan; Nusret Ahmet Muslim (Turkish Economic Association, 2006)
The high credit card interest rates in Turkey attracted considerable attention in recent years to regulate the Turkish credit card industry. Before any regulation decision taken, there needs to be better conceptualization and analysis of the Turkish credit card market. This paper sheds some light in this direction. First, we highlight the most striking aspects of the Turkish credit card market. After exposing the problem, we benefit from the existing theoretical and empirical studies on the structure of competition in the credit card industry. Potential reasons for the lack of competitions are denoted. Having the existing studies in mind, we finally, construct an empirical model to estimate the market structure in the Turkish credit card industry. Newly disseminated data on the Turkish credit card industry is first introduced in this paper. Our empirical results are based on the panel data set of 22 banks from the second quarter of 2001 to the third quarter of 2005. In addition to random and fixed effects regressions, instrumental variable fixed effect regressions are run on this sample. Our results robustly conclude that the credit cards interest rates in Turkey are economically insensitive to the changes in the cost of fund. This result indicates that Turkish credit card market is characterized with lack of strong competition and hence suggests some regulatory measures.
Keywords: F21; G21; O19; 330; Credit Cards; Regulation; Supervision; Financial Markets; Banking; Competition Market Structure.